Comportamiento agronómico del cultivo de pimiento (capsicum annum l.) con diferentes abonos orgánicos en la Unidad Educativa Calazacón de Santo Domingo de los Tsáchilas, año 2014 - Parrales Valenzuela, David Alexander (2015)
This research was conducted in Education Unit Calazacón of Santo Domingo de los Tsáchilas, 2014, the variables evaluated were: plant height, weight, fruit length and diameter, number of fruits and number of crops. Established treatments were 1, 3 and 5 kg of vermicompost; 1.3 to 5 kg of water hyacinth plus a control, this dose given per square meter. The results show that at the end of the investigation with the results it was established that the best level of organic fertilizer on pepper production was treatment 3 (5 kg of humus) shown in the variables evaluated for plant height, number of weight harvest, length, weight and fruit diameter. The best agronomic performance of pepper crop was established in treatment with 5 kg of vermicompost with plant height of 46.00 cm; fruits per harvest with 4.50, 7.75 and 5.75 fruits per plant; fruit weight with 76.80, 88.91 and 77.03 grams in three crops; fruit along with 11.68, 12.48, 11.95 cm and diameter of fruit with 4.70; 4.99 and 4.56 cm. The economic analysis of the treatments under study showed that treatment 3 (5 kg of humus) reported higher revenues to $ 117.46; Net income increased to $ 17.35 and better cost benefit ratio with 1.17.